2017
DOI: 10.1007/s11999-016-5140-5
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Limited Health Literacy Ask Fewer Questions During Office Visits With Hand Surgeons

Abstract: Background In the midst of rapid expansion of medical knowledge and decision-support tools intended to benefit diverse patients, patients with limited health literacy (the ability to obtain, process, and understand information and services to make health decisions) will benefit from asking questions and engaging actively in their own care. But little is known regarding the relationship between health literacy and question-asking behavior during outpatient office visits. Questions/purposes (1) Do patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 40 publications
5
80
1
1
Order By: Relevance
“…Our findings support previous work showing that people with lower health literacy have lower motivation to seek new knowledge in the health system (Cashin et al, ). To date, the lower levels of information use and access among people with low health literacy have been attributed to embarrassment or lack of competence (Menendez et al, ). However, our study suggests that their lower desire for being informed about health care could also be an important reason for their passive behavior with regard to information seeking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings support previous work showing that people with lower health literacy have lower motivation to seek new knowledge in the health system (Cashin et al, ). To date, the lower levels of information use and access among people with low health literacy have been attributed to embarrassment or lack of competence (Menendez et al, ). However, our study suggests that their lower desire for being informed about health care could also be an important reason for their passive behavior with regard to information seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy has been shown to be a personal factor contributing to information‐seeking behaviors, which in turn influence knowledge, coping, and self‐care abilities (Lambert & Loiselle, ). Older people with low health literacy have demonstrated less information‐seeking behaviors using digital technologies or print materials compared to those with high health literacy (Manganello et al, ; Von Wagner, Semmler, Good, & Wardle, ), and have shown higher reliance on health‐care providers’ recommendations without seeking further information (Menendez et al, ; Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…One would imagine that the patients with low health literacy would be the very patients for whom additional time and explanation would be most important . Patients with limited health literacy ask fewer questions during office visits, which may lead to shorter visits with the physician . These patients may legitimately have fewer questions, but they also may feel less comfortable asking their questions than patients with more education and higher health literacy.…”
mentioning
confidence: 99%
“…17 Patients with limited health literacy ask fewer questions during office visits, which may lead to shorter visits with the physician. 18 These patients may legitimately have fewer questions, but they also may feel less comfortable asking their questions than patients with more education and higher health literacy. Physicians may feel less connected and less comfortable with patients with educational, cultural, and language differences, which may be more pronounced when managing a patient with limited health literacy.…”
mentioning
confidence: 99%
“…Objective knowledge about the disease is crucial in the decision-making inherent to genetic counseling [15,16] , and limited health literacy is a barrier for patient engagement in the decision-making process [17] . There are very few studies on objective knowledge, especially prior to genetic counseling.…”
mentioning
confidence: 99%